PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID PADA MATERI PERISTIWA PROKLAMASI KEMERDEKAAN INDONESIA DI SMAN 1 SUNGAI TEBELIAN - Nurfitrianty, Sri; Aunurrahman, Aunurrahman; Astuti, Indri (Academy of Education Journal, 2023)
This study aimed to develop an android-based interactive multimedia on the events surrounding the proclamation of Indonesian independence at SMAN 1 Sungai Tebelian, besides that the research also measures the effectiveness of the implementation of the interactive multimedia that has been developed. This research used Research and Development (R&D) method. The interactive multimedia consisted of 2 screens, namely the login page and the home page. The login page contains the school logo, as well as a login menu that can be accessed by students using the NISN and Password, after successfully entering the home menu. The contents of the home menu consist of instructions for using the application, developer profile, followed by student presence. There is a KD menu and learning objectives, teaching materials designed using Canva, and, equipped pictures. On the home screen, there are also learning videos, interactive quizzes, a virtual presentation of the national proclamation museum, and reflections on learning. Furthermore, related to effectiveness in the Pretest and Posttest, the average result of the Pretest was 53.67 and the Posttest was 82.83 so the N-Gain test obtained a result of 0.62 and it can be concluded that Android-based interactive multimedia improves student learning outcomes, including into the medium category. The results of the t-test showed a sig value of 0.000 so the value was less than 0.05 so there was an influence in the use of interactive multimedia on students. on the effect size test, the result was 3.70 and it was concluded that interactive multimedia based on android, the material for the proclamation of Indonesian independence had an effect on the strong effect category or very strong. .